A DFT Exploration of Efficient Catalysts Based on Metal‐Salen Monomers for the Cycloaddition Reaction of CO2 to Propylene Oxide. Issue 16 (6th June 2017) - Wu, Tao; Wang, Tingting; Sun, Lei; Deng, Kaiming; Deng, Weiqiao; Lu, Ruifeng
Abstract: Using quantum chemistry calculations, we explored the interactions between non‐rare earth metal‐salophen complex (M‐Salen) monomers and propylene oxide (PO) and explored the catalytic mechanisms for the cycloaddition reaction of CO2 to epoxides by the M‐Salen monomers. Our theoretical results demonstrated that a larger binding energy for M‐Salen interacting with PO results in a lower apparent barrier height for the cycloaddition reaction. The Cr III ‐Salen monomer possessed the lowest apparent barrier, while the Al III ‐Salen monomer showed the highest barrier along the reaction pathway, which are consistent with experimental results. In addition, a low apparent barrier was found for the Sc III ‐Salen monomer, suggesting another potential conjugated microporous polymer catalyst for CO2 conversion. Abstract : Cycloaddition reaction of CO2 to propylene oxide: the mechanisms for the cycloaddition reaction with CO2 and epoxides based on metal‐Salen monomers. The apparent barrier is different in the reaction by using different metal‐Salen monomer.